2017
DOI: 10.1007/s00442-017-3845-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat features on size-biased predation on salmon by bears

Abstract: Predators can drive trait divergence among populations of prey by imposing differential selection on prey traits. Habitat characteristics can mediate predator selectivity by providing refuge for prey. We quantified the effects of stream characteristics on biases in the sizes of spawning salmon caught by bears (Ursus arctos and U. americanus) on the central coast of British Columbia, Canada by measuring size-biased predation on spawning chum (Oncorhynchus keta) and pink (O. gorbuscha) salmon in 12 streams with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It was also expected that bear-transferred carcasses would occur throughout spawning reaches, particularly in upper portions of streams, across all stream sizes and consist mainly of chum salmon given the bears' preference for the larger size of chum salmon (Frame, 1974). Based on previous work, it was predicted that the magnitude of consumer-transferred carcasses would correlate positively with salmon density (Quinn et al, 2003) and negatively with stream depth due to reduced consumer access to spawning salmon (Andersson and Reynolds, 2017a). The findings presented in this study illustrate how species-specific responses, functional associations between species, and habitat traits can mediate the subsidy effects of salmon across coastal landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…It was also expected that bear-transferred carcasses would occur throughout spawning reaches, particularly in upper portions of streams, across all stream sizes and consist mainly of chum salmon given the bears' preference for the larger size of chum salmon (Frame, 1974). Based on previous work, it was predicted that the magnitude of consumer-transferred carcasses would correlate positively with salmon density (Quinn et al, 2003) and negatively with stream depth due to reduced consumer access to spawning salmon (Andersson and Reynolds, 2017a). The findings presented in this study illustrate how species-specific responses, functional associations between species, and habitat traits can mediate the subsidy effects of salmon across coastal landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen from carcasses of adult salmon can impact the recipient community directly as food and nutrients for consumers, or indirectly through various bottom-up interactions. Salmon-derived nutrients are exported to terrestrial systems through passive deposition, flooding, or transport by bears, wolves, and birds [12][13][14][15][16]. Salmon carcases are colonized by terrestrial invertebrates and this subsidy has been shown to increase invertebrate biomass the following spring [8,17].…”
Section: Introductionmentioning
confidence: 99%